Halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202410637469.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-22
AI Technical Summary
随着高温尼龙应用范围的拓展,对该材料的要求更高,如汽车发动机周边材料和汽车电子部件需保证其长期在湿热等苛刻条件下使用,添加阻燃剂的高温尼龙材料会存在一定的析出问题,会对金属部件造成腐蚀,从而造成严重的短路风险,在高电压和大电流的条件下,存在较大的安全隐患
一、本发明提供的一种无卤阻燃玻纤增强高温尼龙复合材料,复合材料中的基体树脂尼龙6T/6I与尼龙MXD6由于其结构高度相近,经过挤出机熔融共混制备的复合材料相容性极好,尼龙MXD6树脂具有非常高的刚性、流动性,在高温尼龙体系中引入尼龙MXD6能有效改善高温尼龙树脂的流动性,同时能大幅改善高含量玻璃纤维填充下高温尼龙注塑件产品外观浮纤严重的问题,使得树脂注塑件产品可加工性提升且具有高度光洁的外观。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a method for preparing and applying a halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material. Background Technology
[0002] The application of high-temperature nylon in the electronics and electrical appliance industry is a traditional field. In recent years, the integration level of the electronics and electrical appliance industry has further increased, with components becoming smaller and parts becoming more precise. Therefore, glass fiber reinforced high-temperature nylon products are required to have excellent mechanical properties, processability, and halogen-free flame retardant characteristics. With the expansion of the application range of high-temperature nylon, the requirements for this material are even higher. For example, automotive engine peripheral materials and automotive electronic components need to be able to withstand long-term use under harsh conditions such as humidity and heat. High-temperature nylon materials with added flame retardants may have certain precipitation problems, which can cause corrosion to metal parts, resulting in serious short-circuit risks. Under high voltage and high current conditions, there are significant safety hazards.
[0003] With increasing global awareness of environmental protection, aluminum diethylphosphonate has been found to have higher thermal stability and less impact on the mechanical properties of the matrix resin compared to halogen-free flame retardants such as red phosphorus, melamine polyphosphate, and melamine cyanurate. It is widely used in halogen-free flame retardant materials with high-temperature nylon as the matrix resin. However, the appearance of fiber floating and precipitation under high temperature and humidity conditions in glass fiber reinforced high-temperature nylon parts prepared with aluminum diethylphosphonate are common industry problems that urgently need to be solved. Summary of the Invention
[0004] To solve the above technical problems, the present invention provides a halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material, its preparation method and application. The halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material prepared by the method of the present invention has high mechanical properties, excellent flame retardant effect and no precipitation under long-term high humidity and heat conditions. Products injection molded from this composite material have good appearance.
[0005] The objective of this invention is achieved through the following technical solution: Halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material, comprising the following parts by weight: 30-50 parts of high-temperature nylon resin; 6-10 parts of nylon MXD6 resin; 30-50 parts glass fiber; 7-11 parts of halogen-free flame retardant; 1-3 parts of anhydrous sodium acetate; Other additives: 0.5-2 parts.
[0006] Preferably, the high-temperature nylon resin is nylon 6T / 6I with a melting point of 300-330℃.
[0007] Preferably, the nylon MXD6 resin is formed by the condensation polymerization of m-phenylenediamine and adipic acid, and has a melting point of 230-240°C.
[0008] Preferably, the halogen-free flame retardant is aluminum diethylphosphinate.
[0009] Preferably, the glass fiber is chopped alkali-free glass fiber with a diameter of 8-12 μm and a length of 3-5 mm.
[0010] Preferably, the other additives are one or more of antioxidants, heat stabilizers, and lubricants.
[0011] Preferably, the antioxidant is selected from one or more of hindered phenolic antioxidants, hindered amine antioxidants, and phosphonates. Preferably, the heat stabilizer is selected from one or more of inorganic copper salt heat stabilizers and organic copper salt heat stabilizers.
[0012] Preferably, the lubricant is selected from one or more of erucamide, stearate, stearate, polyethylene wax, polypropylene wax, and silicone powder.
[0013] The preparation method of halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material includes the following steps: S1: Weigh each component according to the ratio, and mix all components except glass fiber and flame retardant together to obtain a premix; S2: The premix, glass fiber and flame retardant from step S1 are fed into an extruder for melt blending, extrusion, granulation and drying to obtain the halogen-free flame retardant glass fiber reinforced high-temperature nylon composite material.
[0014] Preferably, the extruder is a twin-screw extruder. The premix from step S1 is fed into the main feed port of the twin-screw extruder, while glass fiber is added into the first side feed port of the twin-screw extruder and flame retardant is added into the second side feed port. The mixture is then melt-blended, extruded, granulated, and dried to obtain the halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material.
[0015] Preferably, the mixing equipment is a high-speed mixer with a speed of 200-500 rpm and a mixing time of 3-10 min; the twin-screw extruder has a processing temperature of 260-350℃ and a screw speed of 200-500 rpm.
[0016] Preferably, the mixing equipment is a high-speed mixer with a speed of 300-400 rpm and a mixing time of 5-8 min; the twin-screw extruder has a processing temperature of 270-320℃ and a screw speed of 250-350 rpm.
[0017] Application of halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite materials in the preparation of automotive parts and electronic and electrical products.
[0018] The beneficial effects of this technical solution are as follows: I. This invention provides a halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material. The matrix resins nylon 6T / 6I and nylon MXD6 in the composite material have very similar structures. The composite material prepared by melt blending in an extruder has excellent compatibility. Nylon MXD6 resin has very high rigidity and fluidity. Introducing nylon MXD6 into the high-temperature nylon system can effectively improve the fluidity of the high-temperature nylon resin. At the same time, it can significantly improve the problem of severe fiber floating in the appearance of high-temperature nylon injection molded products with high glass fiber content, thereby improving the processability of the resin injection molded products and giving them a highly smooth appearance.
[0019] II. This invention provides a halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material. Anhydrous sodium acetate acts as an inhibitor of the amide exchange reaction between nylon 6T / 6I and nylon MXD6, effectively reducing the amide exchange reaction during melt blending. By lowering the processing temperature, the shear temperature of the shear section during melt blending is reduced, thereby reducing the decomposition of the nylon matrix, halogen-free flame retardant, and other additives, ultimately ensuring that the mechanical properties of the prepared composite material are not compromised. This invention uses nylon MXD6 resin with high gas barrier properties to prevent oxygen from contacting the halogen-free flame retardant, while simultaneously improving the compatibility of the halogen-free flame retardant with the nylon matrix and glass fiber. This allows for better dispersion of the flame retardant in the nylon matrix and glass fiber, enabling the preparation of a V-0 flame-retardant glass fiber reinforced high-temperature nylon composite material with good appearance, excellent processing performance, no loss of mechanical properties, and no precipitation under prolonged high temperature and humidity conditions, without the use of flame retardant synergists, and with a relatively small amount of flame retardant added. Detailed Implementation
[0020] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0021] The raw materials used in the embodiments and comparative examples of this invention are all commercially available, but are not limited to these materials: Nylon 6T / 6I: Grade SH560HF, melting point 310℃, manufacturer is Chengdu Shenghong New Material Technology Co., Ltd.; Nylon 6T / 66: Grade SL1245, melting point 310℃, manufacturer is Qingdao Sanlibenuo New Material Co., Ltd.; Nylon MXD6: Grade M30m, melting point 235℃, manufacturer is Beijing Anaiji Energy Engineering Technology Co., Ltd.; Nylon 66: Grade EP158, melting point 260℃, manufacturer is Zhejiang Huafeng; Halogen-free flame retardant: aluminum diethylphosphinate, grade HR8844, manufactured by Weihai Hairun New Material Technology Co., Ltd. Halogen-free flame retardant: melamine polyphosphate, brand name JLS-PNA350, manufactured by Hangzhou Jiersi Flame Retardant Chemical Co., Ltd. Glass fiber: grade ECS301HP-3-H, manufacturer: Chongqing International Composite Materials Co., Ltd. Anhydrous sodium acetate: analytical grade, manufactured by Tianjin Bodi; Antioxidant: Brand name 1098, manufacturer: Lianlong; Antioxidant: Brand name 168, manufacturer is Lianlong; Heat stabilizer: Grade H3336, manufacturer Brügmann; Lubricant: Silicone powder, brand name GM-100, manufactured by Zhonglan Chenguang Chemical Research and Design Institute.
[0022] The preparation methods of the embodiments and comparative examples of the present invention are as follows: S1: Weigh each component according to the proportions in Table 1 and Table 2. First, premix all components except glass fiber and flame retardant in a high-speed mixer to obtain a premix. S2: The premix from step S1 is fed into the main feed port of a twin-screw extruder, glass fiber is added into the first side feed port of the twin-screw extruder, and flame retardant is added into the second side feed port. The mixture is then melt-blended, extruded, granulated, and dried to obtain the halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material.
[0023] The high-speed mixer operates at 300 rpm for 5 minutes. The twin-screw extruder is a TSS-40 co-rotating twin-screw extruder with a screw length-to-diameter ratio of 48:1, a processing temperature of 270-320℃, a screw speed of 250 rpm, and a production capacity of 100 kg / h.
[0024] Table 1 Formulation Table of Examples Table 2 Comparative Formulation Table Performance testing, relevant testing standards and methods are as follows: (1) Appearance After drying the samples of the examples and comparative examples at 120°C for 4 hours, they were injection molded into discs with a diameter of 10 mm and a thickness of 2 mm. The degree of fiber floating on the surface of the discs was observed with the naked eye.
[0025] (2) Flame retardant properties Flame retardancy performance was tested using the UL-94 flammability standard, with test specimens of 0.8 mm and 1.6 mm thickness.
[0026] (3) Flame retardant precipitation After drying the samples of the examples and comparative examples at 120°C for 4 hours, they were injection molded into discs with a diameter of 10 mm and a thickness of 2 mm. The discs were then placed in a high temperature and high humidity test chamber (85°C, 85RH) and removed after 1000 hours. The flame retardant precipitation on the surface of the discs was then observed with the naked eye.
[0027] (4) Tensile strength The samples from the examples and comparative examples were dried at 120°C for 4 hours and then injection molded into standard specimens for tensile strength testing. The specimen thickness was 4 mm, and the standard number was ISO 527. (5) Bending strength The samples from the examples and comparative examples were dried at 120°C for 4 hours and then injection molded into standard specimens for bending strength testing. The specimen thickness was 4 mm, and the standard number was ISO 178. (6) Impact strength of cantilever beam with notch The samples from the examples and comparative examples were dried at 120°C for 4 hours and then injection molded into standard specimens for cantilever beam notched impact strength testing. The specimen thickness was 4 mm, and the standard number was ISO 180. The test results of Examples 1-6 and Comparative Examples 1-6 are shown in Table 3 below.
[0028] Table 3 Performance results of the examples and comparative examples As can be seen from Examples 1-6, within the scope of the technical solution provided by this invention, the obtained halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material has good appearance and excellent mechanical properties. When the amount of halogen-free flame retardant added is 9 parts, 30 parts of glass fiber filler achieve a flame retardant level of 1.6 mm; when the amount of halogen-free flame retardant added is 11 parts, 30 parts of glass fiber filler achieve a flame retardant level of 0.8 mm; when the amount of halogen-free flame retardant added is 7 parts, 50 parts of glass fiber filler achieve a flame retardant level of 1.6 mm; and when the amount of halogen-free flame retardant added is 8 parts, 50 parts of glass fiber filler achieve a flame retardant level of 0.8 mm. The amount of aluminum diethylphosphonate added is small and no flame retardant synergist needs to be added. No precipitation occurs under 1000h high temperature and high humidity test, which can meet the application requirements of automotive parts and electronic and electrical products under extreme conditions.
[0029] Compared to Example 2, Comparative Example 1 did not use anhydrous sodium acetate, and lacking an amide inhibitor, its mechanical and flame-retardant properties were somewhat compromised. Because nylon 6T / 6I and nylon MXD6 have similar structures, a strong amide exchange reaction occurs during melt blending. The carboxylic acid and secondary amine further crosslink under high temperature and high shear, thus reducing product performance. This invention uses anhydrous sodium acetate as an inhibitor of the amide exchange reaction between nylon 6T / 6I and nylon MXD6, effectively reducing the amide exchange reaction during melt blending, lowering the processing temperature in the shear stage, and reducing the decomposition of flame retardants and other additives. This results in a halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material with good appearance, excellent mechanical properties, low flame retardant content, and V-0 halogen-free flame retardancy. Furthermore, anhydrous sodium acetate is readily available and inexpensive, thus reducing product costs.
[0030] Compared with Example 1, the matrix resin of Comparative Example 2 was changed from Nylon 6T / 6I to Nylon 6T / 66. The performance of Comparative Example 2 was the same as that of Comparative Example 1. However, compared with Example 1, both mechanical properties and flame retardant properties were lacking, indicating that anhydrous sodium acetate is not suitable as an amide exchange inhibitor for Nylon 6T / 66 and Nylon MXD6.
[0031] Compared with Example 4, Comparative Example 3, with high glass fiber filling, had its matrix resin changed from Nylon 6T / 6I to Nylon 6T / 66. The appearance and flame retardant properties of Comparative Example 3 were somewhat compromised due to the change in matrix resin.
[0032] Compared to Example 5, Comparative Example 4 did not contain nylon MXD6 resin, resulting in severe fiber floating and decreased flame retardant performance. Furthermore, flame retardant began to precipitate under high temperature and humidity conditions. Nylon MXD6 resin possesses very high rigidity, flowability, and gas barrier properties. Adding 6-10 parts of nylon MXD6 resin to high-temperature nylon resin, due to the similarity between the 6I structure "poly(hexamethylene isophthalamide)" in nylon 6T / 6I resin and the structure "poly(m-phenylene adipamide)" in nylon MXD6 resin, results in a composite material with excellent compatibility after melt blending via extrusion. This effectively improves the flowability of high-temperature nylon resin without affecting its mechanical properties, and significantly improves the severe fiber floating defects in high-glass fiber filled high-temperature nylon injection molded parts, resulting in a highly smooth surface finish.
[0033] Compared with Example 4, Comparative Example 5 replaced nylon MXD6 resin with nylon 66 resin. With glass fiber filling, nylon 66 resin could not improve the product appearance and flame retardant performance. At the same time, since the compatibility between nylon 66 and nylon 6T / 6I is not as good as that of nylon MXD6, the mechanical properties of the product decreased.
[0034] Compared to Example 2, Comparative Example 6 replaced the halogen-free flame retardant with melamine polyphosphate. The resulting composite material exhibited inferior flame retardant properties compared to aluminum diethylphosphinate. Under high temperature and humidity conditions, the flame retardant began to precipitate, and the mechanical properties of the composite material decreased. The alkyl portion of aluminum diethylphosphinate showed good compatibility with the long alkyl chains of Nylon 6T / 6I and Nylon MXD6, and its dispersion effect was better than other common halogen-free flame retardants when added alone. Furthermore, due to the high processing temperature of halogen-free flame-retardant high-temperature nylon, the use of flame retardant synergists such as ammonium polyphosphate and zinc borate can cause a certain degree of decomposition during processing, resulting in yellowing and blistering of the product. Long-term use of the product under high temperature and humidity conditions may lead to a certain degree of precipitation, causing corrosion to the metal and posing a significant safety hazard. This invention uses high-barrier nylon MXD6 resin to prevent oxygen from contacting the flame retardant, while improving the compatibility of the flame retardant with the resin and glass fiber. This allows the flame retardant to be better dispersed in the resin and glass fiber, enabling the preparation of a V-0 flame-retardant glass fiber reinforced high-temperature nylon composite material with good appearance, excellent mechanical properties, and no precipitation under high temperature and high humidity conditions, without the use of flame retardant synergists.
[0035] Analysis of data from both the examples and comparative cases demonstrates that nylon MXD6 effectively improves the appearance of loose fibers in halogen-free flame-retardant glass fiber reinforced high-temperature nylon products and enhances their flame retardancy. Furthermore, due to its excellent barrier properties and dispersibility, nylon MXD6 effectively prevents the precipitation of flame retardants under high temperature and humidity conditions. Anhydrous sodium acetate, as an inhibitor of the amide exchange reaction, reduces the frequency of the amide exchange reaction between nylon 6T / 6I and nylon MXD6 during melt blending under high temperature and high shear conditions, resulting in halogen-free flame-retardant glass fiber reinforced high-temperature nylon composites with excellent mechanical properties.
[0036] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications or equivalent changes made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material, characterized in that: The materials include the following parts by weight: 30-50 parts of high-temperature nylon resin; 6-10 parts of nylon MXD6 resin; 30-50 parts glass fiber; 7-11 parts of halogen-free flame retardant; 1-3 parts of anhydrous sodium acetate; Other additives: 0.5-2 parts; The high-temperature nylon resin is nylon 6T / 6I, with a melting point of 300-330℃; The halogen-free flame retardant is aluminum diethylphosphinate.
2. The halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material according to claim 1, characterized in that: The nylon MXD6 resin is formed by the condensation polymerization of m-phenylenediamine and adipic acid, and has a melting point of 230-240℃.
3. The halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material according to claim 1, characterized in that: The glass fiber is a short-cut alkali-free glass fiber with a diameter of 8-12 μm and a length of 3-5 mm.
4. The halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material according to claim 1, characterized in that: The other additives are one or more of antioxidants, heat stabilizers, and lubricants.
5. The method for preparing the halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material according to any one of claims 1-4, characterized in that, Includes the following steps: Step S1: Weigh each component according to the ratio, and mix all components except glass fiber and flame retardant together to obtain a premix; Step S2: The premix, glass fiber and flame retardant from step S1 are fed into an extruder for melt blending, extrusion, granulation and drying to obtain the halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material.
6. The halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite material according to any one of claims 1-4, characterized in that: Application of halogen-free flame-retardant glass fiber reinforced high-temperature nylon composite materials in the preparation of automotive parts and electronic and electrical products.
Citation Information
Patent Citations
Method for manufacturing polyamide resin composition
JP2003105095A